2022
DOI: 10.1002/pbc.29602
|View full text |Cite
|
Sign up to set email alerts
|

FDA approval summary: Crizotinib for pediatric and young adult patients with relapsed or refractory systemic anaplastic large cell lymphoma

Abstract: In January 2021, the U.S. Food and Drug Administration (FDA) approved crizotinib for pediatric patients 1 year and older and young adults with relapsed or refractory systemic anaplastic large cell lymphoma (sALCL). This is the first approval for pediatric sALCL. Approval was based on a single-arm trial of crizotinib monotherapy that included 26 patients, aged 1-20 years, with previously treated sALCL. Efficacy was based on centrally assessed objective response rate (88%) and duration of response.Herein, we hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The ADVL0912 phase I/II study on 26 children receiving crizotinib for ALK-positive ALCL noted treatment-related grade ≥3 neutropenia (61.5%), lymphopenia, febrile neutropenia, myositis, and skin infection cases (3.8% each; no severe infection in the low-dose group) [ 144 ]. A commentary on ADVL0912 stated that rates of severe cytopenias may rise with exposure and that upper respiratory infections are commonly seen with crizotinib treatment (31%; no severe case) [ 145 ]. Combination of crizotinib with cytotoxic chemotherapy in the ADVL1212 phase I study for children with refractory solid tumors or ALCL demonstrated high rates of severe infections (20.5%) and febrile neutropenia (38.5%) [ 146 ].…”
Section: Tyrosine Kinase Inhibitors (Tkis)mentioning
confidence: 99%
“…The ADVL0912 phase I/II study on 26 children receiving crizotinib for ALK-positive ALCL noted treatment-related grade ≥3 neutropenia (61.5%), lymphopenia, febrile neutropenia, myositis, and skin infection cases (3.8% each; no severe infection in the low-dose group) [ 144 ]. A commentary on ADVL0912 stated that rates of severe cytopenias may rise with exposure and that upper respiratory infections are commonly seen with crizotinib treatment (31%; no severe case) [ 145 ]. Combination of crizotinib with cytotoxic chemotherapy in the ADVL1212 phase I study for children with refractory solid tumors or ALCL demonstrated high rates of severe infections (20.5%) and febrile neutropenia (38.5%) [ 146 ].…”
Section: Tyrosine Kinase Inhibitors (Tkis)mentioning
confidence: 99%
“…In the case of the approval of naxitamab, characterization of DOR was limited by lack of prespecified disease assessments following treatment discontinuation, receipt of further treatment and follow-up at local institutions, and by the administration of subsequent anticancer therapy following onset of response but prior to demonstration of disease progression in some patients [4]. The approval of crizotinib for sALCL also faced limitations in the assessment of DOR as most patients proceeded to transplant [10 ▪ ]. In both these examples, DOR as calculated may be a conservative assessment of the treatment effect, and the review teams determined that sufficient information was provided to support an assessment of DOR, despite limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Efficacy evaluation was based on ORR and DOR observed in 26 patients with sALCL ages 3–20 years old (Table 1) [9]. The assessment of DOR, critical to assessment of ORR as a clinical endpoint, was limited by more than half of patients proceeding to hematopoietic stem cell transplantation (HSCT); data on DOR in the patients who did not proceed to HSCT supported durability of responses [10 ▪ ]. In this case, the review team considered the biologic similarity of the disease in young adults and the inclusion of some young adults in the study population to support extension of the pediatric indication to include young adults [10 ▪ ].…”
Section: Crizotinibmentioning
confidence: 99%
“…Similar results were observed for small molecules. Crizotinib (Xalkori), a multitarget TKI targeting ALK, ROS1, and MET, has been approved for treating relapsed refractory ALCL in children and young adults (24)(25)(26)(27)(28). Approval was obtained based on a high overall response rate (88%), complete response rate (81%), and duration of response, with 67% of patients not undergoing stem cell transplantation reaching at least 6 months of CR.…”
Section: Alk Signaling In Anaplastic Large Cell Lymphomamentioning
confidence: 99%